PENINGKATKAN BERPROSES SISWA DALAM BELAJAR IPS DENGAN TEKNIK “OVAL – ET” - Sad Diana (Khazanah Pendidikan, 2013)
This study aims to: 1) increase the involvement of students in learning activities proceed on Population Problems materials and Abatement Efforts through learning techniques OVAL-ET, 2) improving student learning outcomes in social studies learning through techniques OVAL-ET, and 3 ) determine students responses to the application of learning to OVAL-ET techniques in social studies for VIII A grade students of SMP Negeri 2 Rawalo in the first semester in the Academic Year 2010/2011. Questionnaires and interviews were used to collect data about their interests, and the assessment for learning social studies, while the observations are used to collect data about student involvement in various aktvitas proceed to learn both in the classroom and outside the classroom, and learning logs are used to determine students responses to the application of engineering OVAL-ET in teaching social studies. Based on the data from this study concluded Technique "OVAL-ET" to proceed to increase the involvement of students in learning activities and student achievement. Abstrak: Penelitian ini bertujuan untuk : 1) meningkatkan keterlibatan berproses siswa dalam aktivitas belajar pada materi Permasalahan Kependudukan dan Upaya-Upaya Penanggulangannya melalui pembelajaran dengan teknik OVAL-ET; 2) meningkatkan hasil belajar siswa pada pelajaran IPS melalui pembelajaran dengan teknik OVAL-ET; dan 3) mengetahui tanggapan siswa terhadap penerapan pembelajaran dengan teknik OVAL-ET pada mata pelajaran IPS bagi siswa kelas VIII A SMP Negeri 2 Rawalo pada semester I Tahun Pelajaran 2010/2011. Angket dan wawancara digunakan untuk mengumpulkan data tentang minat, dan penilaian pembelajaran IPS selama ini, sedangkan observasi digunakan untuk mengumpulkan data tentang keterlibatan berproses siswa dalam berbagai aktvitas belajar baik di kelas maupun di luar kelas, dan learning logs digunakan untuk mengetahui tanggapan siswa terhadap penerapan teknik OVAL-ET dalam pembelajaran IPS. Berdasarkan data hasil penelitian dapat disimpulkan Teknik “OVAL-ET” dapat meningkatkan keterlibatan berproses siswa dalam berbagai aktivitas belajar dan prestasi belajar siswa. Kata kunci: aktivitas belajar, Ilmu Pengetahuan Sosial, OVAL-ET